Edmodo-Based Blended Learning Media in Learning Mathematics - Helsa, Yullys; Kenedi, Ary Kiswanto (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
This research is motivated by the need of a media that can support student teachers in elementary teacher education in learning mathematics. Therefore, the purpose of this study is to develop Edmodo-based blended learning media in learning mathematics. This research is a research and development (R&D) that uses the ADDIE procedures. This study results a valid, effective and practical Edmodo-based blended learning media in learning mathematics for student teachers in elementary teacher education. It is implied that Edmodo-based blended learning media can be applied by the lecturers to support student teachers‟ learning activities and process.